2007
DOI: 10.1111/j.1524-6175.2007.06689.x
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine and Valsartan Combined and as Monotherapy in Stage 2, Elderly, and Black Hypertensive Patients: Subgroup Analyses of 2 Randomized, Placebo‐Controlled Studies

Abstract: Patients with difficult to control hypertension typically require 2 or more agents to achieve goal blood pressure (BP) levels. Fixed-dose combination therapies with lower doses generally are well tolerated and more effective than higher-dose monotherapy. The authors performed prespecified and post hoc subgroup analyses of 2 double-blind, randomized, placebo-controlled trials that assessed the efficacy and safety of amlodipine and valsartan, alone and in combination, in patients with mild to moderate hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 22 publications
(40 reference statements)
8
69
1
3
Order By: Relevance
“…First, as CCBs and RAS inhibitors effect vasodilation by different mechanisms, their antihypertensive effects are additive when used in combination. [5][6][7][8]64,65 This effect is exemplified by data from a recent trial involving amlodipine and olmesartan medoxomil, which showed that both the absolute BP reductions achieved and the rate of target BP attainment were significantly greater in patients who received combination therapy than in those who received amlodipine monotherapy. 5 It is important to note that, in contrast to many other studies, the target BP in this trial was defined using both diastolic blood pressure and systolic blood pressure (o140/90 mm Hg for the majority of patients; o130/80 mm Hg for those with diabetes).…”
Section: Other Advantages Of Ccb/ras Inhibitor Combination Therapymentioning
confidence: 85%
See 1 more Smart Citation
“…First, as CCBs and RAS inhibitors effect vasodilation by different mechanisms, their antihypertensive effects are additive when used in combination. [5][6][7][8]64,65 This effect is exemplified by data from a recent trial involving amlodipine and olmesartan medoxomil, which showed that both the absolute BP reductions achieved and the rate of target BP attainment were significantly greater in patients who received combination therapy than in those who received amlodipine monotherapy. 5 It is important to note that, in contrast to many other studies, the target BP in this trial was defined using both diastolic blood pressure and systolic blood pressure (o140/90 mm Hg for the majority of patients; o130/80 mm Hg for those with diabetes).…”
Section: Other Advantages Of Ccb/ras Inhibitor Combination Therapymentioning
confidence: 85%
“…This combination, which is recommended for use by the current guidelines, 2,3 is highly effective in reducing BP in hypertensive patients. [4][5][6][7][8] When used as monotherapy, CCBs are associated with a substantial risk of peripheral oedema, 9-12 a side effect that may reduce patient compliance or necessitate switching to a different drug. 13,14 The incidence of oedema in CCB-treated patients can be substantially reduced by addition of an inhibitor of the renin-angiotensin system (RAS), that is, an ARB or an angiotensin-converting enzyme inhibitor (ACEI).…”
Section: Introductionmentioning
confidence: 99%
“…The nifedipine GITS formulation offers, in addition, the advantage of controlled drug release, making it suitable for once‐daily administration, and an observational study suggests that candesartan reduces the risk of cardiovascular disease and heart failure in comparison with another angiotensin receptor blocker (ARB), losartan 16, 18. A placebo arm was included in DISTINCT in accordance with the International Conference on Harmonisation guideline for evaluation of fixed‐dose combination products for the treatment of hypertension and similar to other multifactorial trials of combination antihypertensive therapies 20, 21, 22, 23. DISTINCT demonstrated that initial combination therapy with nifedipine GITS/candesartan cilexetil was more effective in lowering BP and meeting target BP goals (SBP <140 and DBP <90 mm Hg) vs respective monotherapies at the same doses in participants with hypertension.…”
mentioning
confidence: 99%
“…Так, получила обоснования комбинация антагонистов кальция с ингибиторами АПФ, в результате взаимо-действия более значительно уменьшается пульсовое АД и максимально снижается риск развития сердечно-сосудистых осложнений (результаты исследования ASCOT-BPLA). Особое значение получила комбина-ция антагонистов кальция и АРАII, фармакодинами-ческое взаимодействие которых позволяет почти в 2 раза уменьшать частоту развития отеков лодыжек, связанных с применением антагонистов кальция [14].…”
Section: результаты и обсуждениеunclassified